For construction of foundation piles and diaphragm walls for 13 storied (with 3 basements) institutional building for Brac University at holding no Kha 224, Merul Badda, Dhaka-1212. - Brac University (2023)
This agreement made between Brac University and Next Space Ltd. for construction of foundation piles and diaphragm walls for 13 storied (with 3 basements) institutional building for Brac University new campus building project.